Hubungan indeks massa tubuh terhadap kadar gula darah puasa pengunjung lapangan Niti Mandala Renon bulan Juli Tahun 2018 - Dinda Yustisia Dewi; Anak Agung Nengah Subawa; Ni Nyoman Mahartini (Intisari Sains Medis, 2019)
Background: Diabetes Mellitus (DM) is one type of degenerative disease that increases annually in countries around the world. Overweight and obesity can be a risk factor for type 2 diabetes mellitus. The leading cause of obesity is the unbalanced energy between the calories consumed and the calories used.Aim: This study aims to find the relationship between BMI with fasting blood glucose in Niti Mandala Renon field in July 2018.Methods: The study used cross sectional analytic approach, with samples were Niti Mandala field visitors Renon July 2018. The total sample was determined by correlation coefficient formula single sample.Results: Fasting blood glucose levels have an average level of 81.6 mg/dl and data are normally distributed (p> 0.05). There was a positive correlation between BMI with fasting blood glucose levels (r = 0.295; p = 0.015).Conclusion: There is a positive and significant weak correlation between BMI and fasting blood glucose levels of visitors to the Niti Mandala, Renon in July 2018.